An Intelligent Road Traffic Management System Based on a Human Community Genetic Algorithm - Hnaif, Adnan A.; AL-Madi, Nagham; Abduljawad, Mohammad; Ahmad, Amal (2019 IEEE Jordan International Joint Conference on Electrical Engineering and Information Technology (JEEIT), 2019)
Traffic congestions recognized as a significant problem in modern urban cities. Jordan considered as one of the top countries worldwide in terms of frequency of traffic accidents where the increase in the number of vehicles had led to the rise in the number of traffic incidents, involving the increase in fatalities and injuries, but the fixed timers still control the current traffic signals system in Jordan. In this paper, an Intelligent Road Traffic Management System based on Human Community Genetic Algorithm (IRTMS) proposed. The IRTMS compared with the current traffic system in the Hashmet Kingdom of Jordan, which concludes that it has the minimum total time and waiting time compared with the current traffic lights system.